Socio-demographic structure and constraints of Smallholder Dairy farmers in Oyo state, Nigeria (2019)
The contribution of dairy farming to the socio-economic development of Oyo state and Nigeria at large cannot be underestimated; we therefore sought to establish socio-demographic status and constraints of small holder dairy farmers at five milk collection centres built by FC WAMCO in Oyo state, Nigeria. Well structure close ended question-based questionnaires were administered in the study location. Farmer’s demography revealed 63.64% and 36.36% male and female respectively, majority (46.54%) were between 30 and 40yrs. 73.82% do not have formal education, 40.18% reported 10 years of rearing. Major constraints identified were; lack of milking equipment reported by 97.64%, 93.82% reported lack of milk preservation facilities. 97.64% reported high cost of breeder stock. 51.82% were not aware of artificial insemination. Inaccessibility to good water was reported by 98.55%, 93.09% reported cattle rustling, 70% were not aware of any biosecurity measures.